Commercial iconography of sport - Eguizábal Maza, Raúl (Historia y Comunicación Social, 2012)
The aim of this article is the study of the relationships between sport and advertising through the images of advertising graphics, using for this purpose the iconological method. Three types of links that correspond to three different historical periods are set to do so. And images are studied both in their relationship with other prior or contemporaneous which serves as a study, and through a process of contextualisation; studying the images in the light of the relationship with the texts that accompany them (the verbal record of the announcement) and with the situation (communicative and sociocultural) as they occur.
Keywords: Iconography; history; sport; advertising; image.